2015
DOI: 10.1016/j.tiv.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric assessment of toxicant induced neuronal degeneration in full and restricted contact co-cultures of embryonic cortical rat neurons and astrocytes: Using m-Dinitrobezene as a model neurotoxicant

Abstract: With m-Dinitrobenzene (m-DNB) as a selected model neurotoxicant, we demonstrate how to assess neurotoxicity, using morphology based measurement of neurite degeneration, in a conventional “full-contact” and a modern “restricted-contact” co-culture of rat cortical neurons and astrocytes. In the “full-contact” co-culture, neurons and astrocytes in complete physical contact are “globally” exposed to m-DNB. A newly emergent “restricted-contact” co-culture is attained with a microfluidic device that polarizes neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…The findings of the present study provide further support for other published literature 6,7,[23][24][25][26][27] demonstrating the protective/ameliorative effects to toxins/toxicants of coculturing neuronal-astrocyte cells, and specifically does so in a transwell/restricted contact model (as applied in this study), for which there are limited other publications, 6,25,28 as well doing so using human-derived cells 8,9,29 instead of rodent-derived cells.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of the present study provide further support for other published literature 6,7,[23][24][25][26][27] demonstrating the protective/ameliorative effects to toxins/toxicants of coculturing neuronal-astrocyte cells, and specifically does so in a transwell/restricted contact model (as applied in this study), for which there are limited other publications, 6,25,28 as well doing so using human-derived cells 8,9,29 instead of rodent-derived cells.…”
Section: Introductionsupporting
confidence: 89%
“…These findings are in agreement with literature data, although still limited in this area, on neuroprotection effects by astrocytes on neurons, that evaluated different end points and compounds (eg, 6-hydroxydopamine, tributyltin, trimethyltin, 2,5-hexanedione, MeHg, MGO, m-dinitrobenzene, and small iron oxide particles) using different co-culture models. 6,7,[23][24][25][26][27] In particular, these CNS co-culture models apply primary rodent astrocytes and neurons or mixture of primary/ immortalized rodent astrocytes and human neurons mainly by using 2 methods of co-culture:…”
Section: Discussionmentioning
confidence: 99%
“…At power densities of 68 and 101 W/mm 2 , however, morphological neurite alterations occurred in and around the NIR-focused region. The observed morphological changes were neurite transection, beading, and fragmentation, which were used as indicators of neurite injury and degeneration in cultured nerve cells [25][26][27] . At the highest power level of 101 W/mm 2 , it was found that the surrounding agarose hydrogel also melted due to the thermoplasmonic heat.…”
Section: Resultsmentioning
confidence: 99%
“…Microfluidic devices with semblance to Teflon Campenot chambers, parse soma and neurites into separate compartments linked by a series of grooves that serve as a passageway for neurites. These unique segregated culture schemes have been broadly adapted as in vitro models for axonal injury [1], axonal transport [2], and neurite-glia interactions [35]. However, slight deviations in device geometry among these Campenot-like microfluidic devices induce vastly different nutrient transport profiles that influence cell viability and neurite extension, and there is limited work offering a detailed rationale for these observations.…”
Section: Introductionmentioning
confidence: 99%